Level of Autonomy and Antenatal Services Utilization among the Women of Reproductive age Group Residing in an Urban Municipality of Lalitpur - Maharjan, Reena; Bharati, Mamata; Shrestha, Sarala; Tandukar, Bimala; Parajuli, Bimala; Singh, Shreejana (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Antenatal care is one of the pillars of a safe motherhood programme in improving maternal and child health. Women’s autonomy is seen as an important factor in utilization of maternal health services. Therefore, the objective of study was to find the level of autonomy and utilization of antenatal services among the women of reproductive age group. Methods: A descriptive cross-sectional study design was used. A total of 151 women of reproductive age group having at least one child in the age group of less than one year were selected using non probability purposive sampling technique from four randomly selected wards of Godawari Municipality. A validated and pretested Nepali version interview schedule was used to collect data from the respondents through door-to-door visit. Descriptive statistics such as frequency, percentage, mean, standard deviation and inferential statistics i.e. Fisher’s exact test was used to analyze data. Results: The study findings revealed that the majority (58.3%) of respondents had a lower level of overall autonomy. The highest autonomy was seen in decision making and lowest in financial related issues. Almost all (96%) of the respondents had fully utilized antenatal services. There was significant association between antenatal services utilization with women’s autonomy (p-value 0.041). Education of women and their husbands (p-value 0.009 and 0.013 respectively) as well as easy access to health facilities and availability of private transportation (p-value 0.005 and 0.039 respectively) were significantly associated with utilization of antenatal services. Conclusions: This study concludes that women’ autonomy tends to influence their antenatal services utilization. Likewise, education of women as well as their husbands tends to facilitate utilization of antenatal services. The study also concludes that easy access to health facilities and availability of private vehicles facilitates utilization of antenatal services.